VERBAL LANGUAGE STYLE ANALYSIS AND VISUAL ANALYSIS ON BANK ADVERTISEMENTS IN INDONESIA - Sri Nurbani; Yelly A Barlian; M Hidayatullah (Balong International Journal of Design, 2020)
ABSTRACT The progress of the world is growing rapidly from year to year, as the world economic level continues to grow in Indonesia, both private and central and local governments. In its development banking compete to capture its customers. One of the most powerful ways is to advertise their products through various media. The advertiser creates a compelling creative strategy to deliver a message that is compelling and accepted by the target audience, so the goal of banking can be achieved, which is to reach many customers. This phenomenon draws the author's attention to researching the language styles as well as the visual techniques that the ad creator has promoted as one of its creative strategies. The purpose of this research is useful to solve a problem that relates to the creation of ads related to verbal and visual language, in this case related to the style of the language used both verbal and visual. This research uses qualitative methods of descriptive. The results obtained from this study are the dominant language style used by advertisers is a rhetoric with an aliteracy as the figure of speech. Meanwhile, visual language if viewed from visual perception is using Similarity, Continuation, and Proximity as a way of affirmation of messages listed on the tagline. Keywords: Banks, language styles, visuals, creative strategies, advertising